DESIGN AND DEVELOPMENT OF NON-ISLAMIC CULTURE PHOTOBOOK DOCUMENTASION IN EARTH USING R&D METHOD - Jacky Jacky (Universitas Internasional Batam, 2022)
Photo books are a type of book that is used to share photographic products with a lot of documentation value. Photo books can be used to convey or communicate information about the themes discussed. Non-Islamic civilizations are featured in a photo book called Malay Earth. Riau is notable for being the largest Malay country in the state of Riau. To aid the research process, the author employs the Research & Development technique. Photo albums can serve as an everlasting reminder of a photographer's work. The photo book's development has received excellent feedback, as it depicts every race and ethnic culture practiced by numerous non-Islamic cultural groups in malay enviroment.